2011
DOI: 10.1007/s12043-011-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

Energy-dispersive X-ray fluorescence – A tool for interdisciplinary research

Abstract: Trace elements have been at the focus of attention for decades with considerable emphasis on their role in biology and biomedical sciences, environmental sciences, geology, archaeology and material sciences. They comprise a large number of elements, some having essential physiological functions, whereas others are toxic, mutagenic or carcinogenic. A few even have antiproliferative and anticarciniogenic properties. The advent of various instrumental techniques and sophisticated instrumentations has made their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…[34][35][36]. This is consistent with the observations of Sharifi and Pirsa [37] who found that the complete degradation of pectin occurs in the temperature range of 180 to 450 • C.…”
Section: Thermogravimetry (Tga)supporting
confidence: 92%
See 1 more Smart Citation
“…[34][35][36]. This is consistent with the observations of Sharifi and Pirsa [37] who found that the complete degradation of pectin occurs in the temperature range of 180 to 450 • C.…”
Section: Thermogravimetry (Tga)supporting
confidence: 92%
“…Then, owing to the low decomposition temperature of hemicellulose, lignin, and pectin, a degradation temperature close to 262 • C is observed, which ends up with a significant drop around 324 • C, showing a residual mass corresponding to carbonous compounds[34][35][36]. This is consistent with the observations of Sharifi and Pirsa[37] who found that the complete degradation of pectin occurs in the temperature range of 180 to 450 • C.…”
supporting
confidence: 89%
“…The spectra were collected for a sufficiently long time so that good statistical accuracies can be achieved. The quantitative analysis is carried out using nEXT software (Sudarshan et al, 2011).…”
Section: Experimental Energy Dispersive X-ray Fluorescence (Edxrf) Analysismentioning
confidence: 99%
“…X-ray fluorescence: Energy dispersive X-ray fluorescence (EDXRF) in solid state analyses were used to determine and compare the elemental composition of the sponge material, the silica purified from sponges, as well as commercial silica used for open column chromatography. This technique allows for fast multi-elemental analyses, detecting major and trace elements, and is used in a wide range of studies [27,28].…”
Section: Sample Characterizationmentioning
confidence: 99%